Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1039/d2nr02955c
|View full text |Cite
|
Sign up to set email alerts
|

Structure-dependent high-TC ferromagnetism in Mn-doped GeSe

Abstract: Layered IV-VI diluted magnetic semiconductors (DMSs) have exhibited fascinating ferromagnetism down to atomic layers, but their relatively low Curie temperature (TC, ≤200 K) significantly hinders their practical application. In this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
(91 reference statements)
1
3
0
Order By: Relevance
“…The calculated magnetic moments and spin charge density (∆ρ = ρ up − ρ down ) distributions in Figure 6 show that all the doped GeSe MLs are magnetic. Our results indicate that single doping of Mn results in a magnetic moment of 5.0 µB in (Ge, Mn) Se ML, which mainly comes from the spin-up electrons around Mn, consistent with previous theoretical results [16,17] and slightly larger than the 4.25 µB observed in GeMnSe nanocombs in previous experimental studies [35]. Mn-Cl and Mn-Br co-doping further weakened the magnetic moment to 4.0 µB in both cases by introducing more spin-down electrons in (Ge, Mn) (Se, Cl) and (Ge, Mn) (Se, Br) MLs.…”
Section: Dopantsupporting
confidence: 93%
“…The calculated magnetic moments and spin charge density (∆ρ = ρ up − ρ down ) distributions in Figure 6 show that all the doped GeSe MLs are magnetic. Our results indicate that single doping of Mn results in a magnetic moment of 5.0 µB in (Ge, Mn) Se ML, which mainly comes from the spin-up electrons around Mn, consistent with previous theoretical results [16,17] and slightly larger than the 4.25 µB observed in GeMnSe nanocombs in previous experimental studies [35]. Mn-Cl and Mn-Br co-doping further weakened the magnetic moment to 4.0 µB in both cases by introducing more spin-down electrons in (Ge, Mn) (Se, Cl) and (Ge, Mn) (Se, Br) MLs.…”
Section: Dopantsupporting
confidence: 93%
“…Magnetic substrate, magnetic doping, and mixing are common methods for generating magnetism. Magnetic atom-doping-induced magnetism in a GeSe monolayer is an effective method; especially, Mn atom doping can even produce ferromagnetism with Curie temperature T c up to 309 K in experiments. However, in these examples, the substitution does not break the C 2 x symmetry operation; hence, it does not meet the condition. Interestingly, computational researches have shown that the substitution of Group V atoms (P, As, and Sb) for the Group IV Ge atom can induce structural distortion and break C 2 x symmetry operation while generating magnetism in the GeSe monolayer. The reason can be attributed to the fact that Group V atoms have an extra electron compared to the Group IV Ge atom, and electron asymmetry leads to magnetic and structural distortions, which have been reported recently .…”
Section: Resultsmentioning
confidence: 99%
“…2D magnets can provide novel opportunities for the development of spintronics. Very recently, large-scale 2D magnetic materials with above room-temperature ferromagnetism have been reported in Mn-doped GeSe films, 14 vacancy-incorporated MoSe 2 , 15 and strain-mediated MoS 2 16 and ReS 2 17 films, but their practical applications remain a challenge owing to limited controllability, which indicates that the investigation of 2D intrinsic magnets is imminent. The experimental findings of 2D vdW FM Cr 2 Ge 2 Te 6 , 11 CrI 3 18 and AFM FePS 3 19 with atomic layer thickness immediately lifted the curtain and triggered a wave of research on 2D vdW magnets.…”
Section: Introductionmentioning
confidence: 99%